Cultural Theory and History: Sign and Context - Jewdokimow, Dorota; Kizińska, Karolina (Wydawnictwo Naukowe Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
Sign and Context is the next book of the series “Cultural Theory and History,” initiated during a seminary on this topic held in Institute of Cultural Studies at Adam Mickiewicz University. Two studies presented here are focused on the topic of historical construction of meaning, using the theoretical propositions of Moscow-Tartu school on the example of the semiotics of shame and according to the vision of social negotiation of meaning on the example of gender characteristics of musical culture.
Keywords: culture; semiotics; shame; Moscow-Tartu school; musical culture; gender; cultural history